2016
DOI: 10.1111/nph.14165
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association analysis reveals distinct genetic architectures for single and combined stress responses in Arabidopsis thaliana

Abstract: Summary Plants are commonly exposed to abiotic and biotic stresses.We used 350 Arabidopsis thaliana accessions grown under controlled conditions. We employed genome‐wide association analysis to investigate the genetic architecture and underlying loci involved in genetic variation in resistance to: two specialist insect herbivores, Pieris rapae and Plutella xylostella; and combinations of stresses, i.e. drought followed by P. rapae and infection by the fungal pathogen Botrytis cinerea followed by infestation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 112 publications
(183 reference statements)
3
48
0
Order By: Relevance
“…Genome‐wide association studies in Arabidopsis revealed that distinct genetic architectures are associated with the tolerance between drought alone and drought combined with herbivory or Botrytis cinerea (Davila Olivas et al ., ). Most of quantitative trait loci (QTLs) underlying combined biotic/abiotic stress responses show distinct or contrasting responses when separately exposed to these stresses (Makumburage et al ., ; Thoen et al ., ), strengthening the view that the genetic architecture underlying plant adaptation to individual and combined stresses is different.…”
Section: Cross‐tolerance or Tradeoffmentioning
confidence: 97%
“…Genome‐wide association studies in Arabidopsis revealed that distinct genetic architectures are associated with the tolerance between drought alone and drought combined with herbivory or Botrytis cinerea (Davila Olivas et al ., ). Most of quantitative trait loci (QTLs) underlying combined biotic/abiotic stress responses show distinct or contrasting responses when separately exposed to these stresses (Makumburage et al ., ; Thoen et al ., ), strengthening the view that the genetic architecture underlying plant adaptation to individual and combined stresses is different.…”
Section: Cross‐tolerance or Tradeoffmentioning
confidence: 97%
“…In addition, GWAS and linkage mapping were used to identify a gene responsible for heavy metal accumulation in the leaves of Arabidopsis (Chao et al ., ). In addition to these genetically simple traits, more complex features have been dissected using GWA mapping, including metabolic networks (Ishihara et al ., ; Wu et al ., ), root and shoot system architecture (Clauw et al ., ), responses to biotic and abiotic stresses (Francisco et al ., ; Ariga et al ., ; Davila Olivas et al ., ; van Rooijen et al ., ), interactions between plants and growth‐promoting microorganisms (Wintermans et al ., ), and the genomic architecture of biomass heterosis (Yang et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that cross between BoZ and BrK would be helpful in creating B. napus with higher glucosinolate content. As reported, the glucosinolates in Arabidopsis and Brassica crops were transported from maternal tissues (e.g., leaves; Nour‐Eldin & Halkier, ; Nour‐Eldin et al, ), and glucosinolates in leaves have been proved with functions in improving stress tolerance, insect and pathogen resistance (Davila Olivas et al, ; Mao et al, ; Xu et al, ). The linoleic acid was greatly increased in all the hybrids but in diploid parents, indicating better oil composition in resynthesized B. napus .…”
Section: Discussionmentioning
confidence: 83%